Real-World, Retrospective, Multicenter, Observational Study on the Use of the First Liquid AbobotulinumtoxinA in Italy - Carlo Di Gregorio; Matteo Tretti-Clementoni; Magda Belmontesi; Marina Romagnoli; Alessandro Innocenti; Malvina Zanchi; Lucia Leone; Giovanni Damiani; Ivano Iozzo (Adis, Springer Healthcare, 2023)
Abstract Introduction Randomized controlled trials (RCTs) suggested that liquid formulation of botulinum toxin type A (aboBoNT-A) is safe and effective, but data confirming these characteristics in a real-life heterogenous set of patients are currently lacking. This study aimed to assess the efficacy and safety of the ready-to-use aboBoNT-A solution in adults with moderate-to-severe glabellar wrinkles. Methods In this real-life, multicenter, retrospective, observational study, healthy adults were treated at baseline only with aboBoNT-A solution on the glabellar area and followed up for 24 weeks. Re-treatment after 20-24 weeks could also be combined with other aesthetic procedures. Family history of immune-mediated inflammatory diseases (IMIDs) was not an exclusion criterion. Patient-reported outcomes (patient's satisfaction and injection-related pain) and physician-reported outcomes (Physician Global Assessment, PGA) were collected. Results Of the 542 patients enrolled in the study, 38 had IMID family history. Injection-related pain was reported in 128 (23.62%) as mild (pain VAS = 1.34 ± 0.87) mainly by non-botulinum toxin treatment-naïve women under 50 years of age. At 48 h, physicians rated the clinical result as "improved" in 64% of patients, conversely 264 patients (48.71%) self-evaluated as "satisfied"/"very satisfied". At 4 weeks a touch-up (< 10 units) was performed in 11 (2.03%) patients and 98.2% were "highly satisfied". Re-treatment was performed in 330 (61.45%) patients, mainly botulinum-experienced, at 20 weeks and in 207 (38.55%), mainly botulinum naïve, at 24 weeks. A total of 403 (74.35%) patients were re-treated with the three-point technique and 201 (37.08%) also received hyaluronic acid filler in the lower central face and middle third. There were no cases of de novo IMIDs. Conclusions Real-world data confirmed that aboBoNT-A is a fast, efficient, durable, reproducible, and easy-to-use drug which is also well tolerated in patients with family history of IMID.